Problem Solving Ability of The Fourth Grade Students in Problem Based Learning On Two Dimensional Figures - Primadoni, Ade Bagus; Suharini, Erni; Mulyono, Mulyono (Journal of Primary Education)
This study has the purpose of testing the effectiveness of the Problem Based Learning (PBL) model on the problem-solving ability of two-dimensional figures. This study applied experimental research with a pre-test – post-test control design model. The population of this study was all of the fourth-grade students of SDN in Batangpretepurposive sampling. The sample of this study was the fourth-grade students of SDN Karangtengah 01 and the fourth-grade students of SDN Kemiri 06. The instrument of data collection used was an essay test. The analysis technique used for analyzing the data was a statistical test of paired sample t-test. The results of this study indicated that the PBL model has effectively improved the students' problem-solving abilities. This is indicated by (1) The classical completeness of problem solving abilities of students in the experimental class using PBL models which reached up to 75%, (2) The average of problem-solving abilities of students in the experimental class with PBL models was more than the average of problem-solving ability of students in the control class using the expository learning models, sig α = 5%, with sig. (2-tailed) of 0.018 since 0.018 < 0.05. therefore, the result is significant, (3) the results of the increase in problem solving ability of the experimental class students using PBL models was indicated by the result of pre-test with the percentage of learning completeness of 51%. whereas, the rest of 49% students did not complete the achievement, then the result of post-test with the result of learning completeness at 80% and the rest of 20% students did not complete, sig α = 5%, with sig. (2-tailed) obtained a score of 0.000 < 0.05. Therefore, it can be concluded that the PBL model is effective on problem-solving abilities of students in the fourth-grade elementary school at two dimension figures material.